The Relationship Between Avoidance Goals and Goal Attainment: A Moderated Mediation Analysis. Issue 3 (2nd July 2020) - Kinoshita, Keita; MacIntosh, Eric; Sato, Shintaro
ABSTRACT: Purpose : The purpose of the study is to examine how the combination of "what" (e.g., mastery- and performance-avoidance goals) and "why" (e.g., external regulation) are related to sport participant's goal attainment. To examine this phenomenon, we used achievement goal theory (AGT) and self-determination theory (SDT). Past research has shown that avoidance goals generally are associated with negative outcomes. In this study, we hypothesized that avoidance goals would positively generate goal attainment through the pathway of effort. Moreover, the indirect association would be moderated by the level of external regulation. Method : Based on a sample of sport participants (N = 390), mediation and moderated mediation analyses were used to test the hypotheses. Result : Both mastery- and performance-avoidance goals were positively related to goal attainment through effort. These relationships were moderated at the value of high and moderate levels of external regulation. Conclusions : The results suggest that, in contrast to the general assumption, avoidance goals are not always detrimental. Rather, the research showed that the combination of avoidance goals and external regulation would be positively associated with goal attainment. This may be the reason that coaches' controlling behaviors (e.g., punishment or reward) are commonly utilized, and some people believe that external regulation is effective in sport. However, the relationships should be carefully interpreted because the associations should not last long and may be an unhealthy way to improve athletes' performance.